Novas habilidades para novos leitores?: aspectos da leitura nas Tecnologias Digitais de Informação e Comunicação - Lazarotto, Fátima Cristina Durante (2022)
This research is an investigation about reading and its relation with Digital Information and Communication Technologies. Its main goal is to analyze the reading and navigation skills necessary for readers in texts on digital media. For this, we have specific objectives: mapping digital competences and skills for digital literacy; investigating the skills that the student has in terms of reading digital media and which they will still need to develop and, finally, organizing the skills matrix for the digital literacy arising from the result of this investigation. The justification for carrying out this research stems from the changes experienced by students who, in the midst of the covid-19 pandemic, had online classes and had reading experiences on digital media. In this context, we understand the need for an education and school experience aimed at teaching reading that incorporates the digital literacy skills that contemporary texts bring. The benefits of this research involve the knowledge of what these skills are and how to develop them, which will be able to direct the work of teachers in this new educational context that emerges during and after the pandemic. Theoretical support is based on authors who have develop studies on reading, digital literacy and reading skills and abilities, such as Chartier (2016), Kalantzis, Cope e Pinheiro (2020), Kleiman (1995, 2004, 2007), Rojo (2004, 2009, 2012), Soares (2002, 2003a, 2006, 2020), Street (2014), Tomitch (2008)